A combination of Material Flow Cost Accounting and design of experiments techniques in an SME: The case of a wood products manufacturing company in northern Thailand - Rungchat Chompu-Inwai (2018)
© 2014 Elsevier Ltd. It is essential for small and medium-sized enterprises to manufacture products using standardized and sustainable methods. The case study company here is a wood products manufacturer, and an analysis of its production process revealed that almost 70% of the wood raw materials used is wasted in the form of chippings, sawdust, off-cuts and defects. The objective of this research study was therefore to apply the Material Flow Cost Accounting (MFCA) and Design of Experiments (DOE) concepts to the case study company, in order to reduce materials consumption and minimize waste. The research methodology was divided into two main parts. The first part employed the MFCA concept to analyze the inefficiencies incurred due to resource use within the production process, as well as the causes of such inefficiencies. In the second part, the opportunities available to reduce these inefficiencies were examined. The DOE concept was used to increase the efficiency of wood raw materials use, with a full factorial experiment used to find the optimal cutting settings, those creating less damage. Three factors were studied and an analysis of variance (ANOVA) was conducted. The results of the experiment have subsequently been put into practice, resulting in a reduction of wood materials losses in the cutting process, as a proportion of total wood materials used, from approximately 69 percent to 54 percent. In conclusion, applying MFCA and DOE helped both increase product quality and reduce the adverse environmental impacts of the case study company's production process, saving costs and improving its competitiveness.